Paauglio politrauma žemdirbystės pramonėje: klinikinio atvejo analizė - Bagdonaitė, Kamilė; Sugintaitė, Emilija; Dekerytė, Inga; Lukošiūtė-Urbonienė, Aušra; Kilda, Artūras (Lietuvos chirurgija, 2023)
Polytrauma is a condition when a patient has sustained multiple injuries, which can lead to disability or death. While the agriculture industry is growing, the number of polytrauma patients in children is increasing as well. It is high-energy traumas when it is important to immediately assess injuries and life-threatening conditions and to start trauma protocols guided treatment. In this article, we present a case of a 17-year-old boy who suffered extensive injuries caused by a straw pellets machine. We discussed the importance of prehospital care, multidisciplinary team involvement, and treatment methods.